1995
DOI: 10.1093/ije/24.2.308
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Exposure to N-Nitrosatable Drugs as a Risk Factor for Childhood Brain Tumours

Abstract: Our findings suggest that no increased risk of childhood brain tumours was associated with maternal exposure to nitrosatable drugs. The study results should be viewed with caution given the imprecision of the point estimates as well as the lack of data on specific timing and dosage of exposure and degree of nitrosatability of drugs taken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…One study on childhood brain tumors found an elevated odds ratio of 1.8 for astrocytoma [5], but this was not confirmed in the current study. However, the odds ratio for neuroblastoma was slightly elevated (odds ratio of 1.36), corresponding to a small risk excess observed in the largest neuroblastoma study to date (odds ratio 1.4, 95 percent CI: 1.0, 1.9) [7].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…One study on childhood brain tumors found an elevated odds ratio of 1.8 for astrocytoma [5], but this was not confirmed in the current study. However, the odds ratio for neuroblastoma was slightly elevated (odds ratio of 1.36), corresponding to a small risk excess observed in the largest neuroblastoma study to date (odds ratio 1.4, 95 percent CI: 1.0, 1.9) [7].…”
Section: Discussionmentioning
confidence: 81%
“…A possible mechanism for the association between diuretics and antihypertensives might be the toxic presence of n-nitroso precursors. N-nitroso is a strong transplancental nervous system carcinogen [25,39] and is known to be an ingredient in some diuretics, e.g., furosemide and hydrochlorothiazid and also antihypertensives such as propanolol [7]. It might also be that, in case of a cancer of the fetus, catecholamine production might be responsible for maternal hypertension followed by the accordant medication [39].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies prior to 2004 did not find statistical evidence for an association between maternal exposure to nitrosable drugs and offspring CBTs. (76, 77) Likewise, a large study published in 2006 that included 1,218 CBT cases and 1,218 controls found little support for an association between CBTs and medications containing amines or amides (OR=1.01; 95% CI 0.82–1.24) overall or for astroglial (OR=1.01; 95% CI 0.78–1.31), PNET (OR=1.09; 95% CI 0.75–1.60), or other glial (OR=1.01; 95% CI 0.71–1.44) subtypes. No significant associations were found when data were analyzed by age group (≤5 vs. >5 years) or class of drugs (barbituates, antiepileptics, antihistamines, neurally active drugs, diuretics, sex hormones, or antiemetics).…”
Section: Environmental Exposuresmentioning
confidence: 99%
“…A possible association between childhood cancer and maternal infections [7][8][9][10][11][12] and/or the maternal use of antibiotics [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] has been investigated in a number of case-control and cohort studies ( Table 1). The studies looked at different exposure periods between 3 months prior to conception and the first month of breastfeeding.…”
Section: Introductionmentioning
confidence: 99%
“…The studies looked at different exposure periods between 3 months prior to conception and the first month of breastfeeding. In summary, the majority of studies did not show a clear evidence for an association between cancer in the offspring and maternal use of antibiotics, as risk estimates were not or only marginally increased [13][14][15][16][17][18][19][20]. Four studies observed increased relative risks but the increase was not statistically significant [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%